2021
DOI: 10.1109/tuffc.2021.3073563
|View full text |Cite
|
Sign up to set email alerts
|

Histotripsy for the Treatment of Cholangiocarcinoma Liver Tumors: In Vivo Feasibility and Ex Vivo Dosimetry Study

Abstract: Histotripsy is a non-invasive, non-ionizing, and nonthermal focused ultrasound ablation method that is currently being developed for the treatment of liver cancer. Promisingly, histotripsy has been shown for ablating primary (hepatocellular carcinoma, HCC) and metastatic (colorectal liver metastasis, CLM) liver tumors in preclinical and early clinical studies. The feasibility of treating cholangiocarcinoma (CC), a less common primary liver tumor that arises from the bile ducts, has not been explored previously… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 42 publications
(85 reference statements)
1
12
0
Order By: Relevance
“…The robotic micropositioner moved the focus between treatment locations, and each point was treated with ~500 pulses. The transducer frequency and treatment PRF used in this study were chosen to minimize the treatment time required to ablate the large STS tumors [6,37], and the treatment dosage was chosen based on previous histotripsy studies for other soft tissue applications [12,14,38,39]. The bubble cloud and tissue effects were monitored during treatment using real-time ultrasound imaging.…”
Section: ) Histotripsy Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The robotic micropositioner moved the focus between treatment locations, and each point was treated with ~500 pulses. The transducer frequency and treatment PRF used in this study were chosen to minimize the treatment time required to ablate the large STS tumors [6,37], and the treatment dosage was chosen based on previous histotripsy studies for other soft tissue applications [12,14,38,39]. The bubble cloud and tissue effects were monitored during treatment using real-time ultrasound imaging.…”
Section: ) Histotripsy Treatmentmentioning
confidence: 99%
“…Histotripsy treatment is typically guided in real-time by ultrasound imaging, allowing the precise, non-invasive targeting of tissues ranging from deep, visceral structures to superficial, subcutaneous tumors. Previous preclinical studies have shown that histotripsy can successfully ablate various tumor types ex vivo and in vivo [4], including prostate [8], kidney [9], bone [10], brain [11], pancreatic [12], and liver tumors [13,14]. Additionally, a recent human clinical trial has shown safe and effective ablation of primary and metastatic liver tumors [15].…”
Section: Introductionmentioning
confidence: 99%
“…No significant adverse events associated with histotripsy were reported for any of the patients. Although histotripsy has been previously studied for the ablation of multiple tumor types [8][9][10][12][13][14][15], ablation of superficial tumors, including STS, presents a unique case for histotripsy due to the close proximity of the skin, which has the potential to be damaged by ablative therapies [24,25,45,46]. In this study, skin injury due to histotripsy was noted in the first patient that was treated, with all subsequent treatments showing no change in the VCOG-CTCAE score after treatment.…”
Section: Discussionmentioning
confidence: 77%
“…The robotic micropositioner moved the focus between treatment locations, and each point was treated with ~500 pulses. The histotripsy treatment parameters employed in this study were chosen based on previous histotripsy studies for other soft tissue applications [12,14,40,41]. The bubble cloud and tissue effects were monitored during treatment using real-time ultrasound imaging.…”
Section: ) Histotripsy Treatmentmentioning
confidence: 99%
See 1 more Smart Citation